Mavericks of Sound: Conversations with Artists Who Shaped Indie and Roots Music - Ensminger, David A. (Rowman & Littlefield Publishers, 2014)
In Mavericks of Sound: Conversations with the Artists Who Shaped Indie and Roots Music, music scholar David Ensminger offers a collection of vivid and compelling interviews with legendary roots rock and indie artists who bucked mainstream trends and have remained resilient in the face of enormous shifts in the music world. As the success of the concerts at Austin City Limits have revealed, the fan bases and crowds for indie and roots music often blur and overlap. In Mavericks of Sound, Ensminger brings to light the highways and byways trod by these music icons over the course of their careers and the ways in which their music-making has been affected by, and influenced, the burgeoning indie and roots music movements. Ranging from seminal modern singer-songwriters to rockabilly renegades and indie rockers, Mavericks of Sound features a set of broad, penetrating, and insightful conversations imbued with a sense of musical history and heritage. Ensminger captures firsthand accounts from singer songwriters like Texas Country musician Tom Russell and first wave indie artist and folk rocker Peter Case; rockabilly artists Junior Brown and the Reverend Horton Heat; American indie rock icons such as 11th Dream Day’s Janet Bean, Pere Ubu’s Dave Thomas, Apples in Stereo’s Robert Schneider, and Swans members Michael Gira and Jarboe; English and New Zealand figures such as folk legend Richard Thompson, The Clean’s David Kilgour and The Waterboys’ Mike Scott; and folk, country and rock legends such as Merle Haggard, Ramblin’ Jack Elliott, Ralph Stanley, Neko Case, and Yo La Tengo. Mavericks of Sound is the perfect work for contemporary indie, roots, Americana, country, and folk music fans who want to understand the unique artistry and unbound passion behind America’s musical innovators that readily broke and remolded rules.